Stability of the Functional Equation Deriving From Quadratic Function in Banach Space - Amrit,; Kumar, Anil; Antil, Manoj Kumar (Communications in Mathematics and Applications, 2024)
In this manuscript, we introduce a quadratic functional equation of finite variable:\begin{align} onumber \sum\limits_{i=1}^m \phi \left(2v_i-\sum\limits_{1 \leq i eq j}^m v_j\right)&=(m-7)\sum\limits_{1 \leq i
Keywords: Banach space; Hyers-Ulam stability; Quadratic functional equation